Cortical Activation During Levitation and Tentacular Movements of Corticobasal Syndrome. Issue 45 (November 2015) - Onofrj, Marco; Bonanni, Laura; Delli Pizzi, Stefano; Caulo, Massimo; Onofrj, Valeria; Thomas, Astrid; Tartaro, Armando; Franciotti, Raffaella
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Levitation and tentacular movements (LTM) are considered specific, yet rare (30%), features of Corticobasal Syndrome (CBS), and are erroneously classified as alien hand. Our study focuses on these typical involuntary movements and aims to highlight possible neural correlates. LTM were recognizable during functional magnetic resonance imaging (fMRI) in 4 of 19 CBS patients. FMRI activity was evaluated with an activation recognition program for movements, during LTM, consisting of levitaton and finger writhing, and compared with the absence of movement (rest) and voluntary movements (VM), similar to LTM, of affected and unaffected arm-hand. FMRI acquisition blocks were balanced in order to match LTM blocks with rest and VM conditions. In 1 of the 4 patients, fMRI was acquired only during LTM and with a different equipment. Despite variable intensity and range of involuntary movements, evidenced by videos, fMRI showed, during LTM, a significant ( P <0.05–0.001) activation only of the contralateral primary motor cortex (M1). Voluntary movements of the affected and unaffected arm elicited the known network including frontal, supplementary, sensory-motor cortex, and cerebellum. Willed movements of the LTM-affected arm induced higher and wider activation of contralateral M1 compared with the unaffected arm. The isolated activation of M1 suggests that LTM is a cortical disinhibition symptom, not involving a network. Higher activation of M1 during VM confirms that M1 excitability changes occur in CBS. Our study calls, finally, attention to the necessity to separate LTM from other alien hand phenomena.